Postgraduate Studies on Lean Management-A Review of Initiatives - Mariusz Bednarek; Aleksander Buczacki; Lukasz Bielakowski; Bartlomiej Gladysz; Mariusz Bryke (MDPI AG, 2020)
The article elaborates upon a successful model of postgraduate studies on lean manufacturing. The subject of the research was nine editions of the Kaizen Academy postgraduate studies organized by the Warsaw University of Technology and the Kaizen Institute in the years 2009-2018, that still enjoys interest in the market. A detailed qualitative analysis of this case, followed by a comparative analysis with other post-graduate programs of this type on the national, European, and global level should make it possible to find what is necessary to launch and actively operate for a long time in the (considerably competitive) market of qualification raising programs related to Lean Management (critical success factors). The study has also identified the differences between a successful program, analyzed in detail, and other available programs described in the literature and on the Internet. This has been achieved through a structured analysis of thirty-nine postgraduate programs identified by querying scientific databases and the Google Internet search engine. Best practices and models of postgraduate education on Lean Management have been discussed, and the thirty-nine programs comprising the identified sample have been compared. Considering the very general level of the data available in terms of the organization of postgraduate programs, it has also been assessed if they follow constructivism and experiential learning paradigms. This has been achieved by including the industrial days/visit indicator in the comparison. Given its high value, it has been identified as a success factor of the postgraduate curriculum on Lean Management.